The presentation structure of “Lahire Naga Tahun” in Wayang Topeng Malang theatrical dance - Rahayuningtyas, Wida (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Dramatari Wayang Topeng shows the diversity of characters, the variety of movements, the diversity of costumes, and the diversity of stories. Dramatari Wayang Topeng show is taken from the Panji story, which is oral literature. 17 stories have been developed by the puppeteers at Padepokan Asmara Bangun, Malang Regency. There is one story that is only performed on certain days, namely the month of Sura, which is the month of reckoning Javanese or Javanese new year, which is entitled Lahire Naga Tahun. The purpose of this research is to describe the presentation structure of "Lahire Naga Tahun" in the Malang mask puppet show. The research method used is descriptive qualitative. The data were collected through observation, interviews, and documentation. The results showed that the Lahire Naga Tahun story is based on the results of the development by the puppeteers consisting of 4 episodes, namely (1) Sekartaji Palsu (Fake Sekartaji), (2) Lahire Panji Laras (the birth of Panji Laras), (3) Sayembara Adu Jago (Adu Jago Competition), and (4) Lahire Naga Tahun (the birth of Naga Tahun). The four episodes are presented consecutively with a show time of approximately 2 hours. Each episode contains several scenes. The Sekartaji Palsu episode consists of 4 scenes, namely Partapan, Kingdom of Rancong Kencana, Jenggala Soldier and Keputren. The Lahire Panji Laras episode consists of 2 stages, namely Kaputren and Lolaras. The Sayembara Adu Jago consists of 2 steps, namely Karang Pradesan and Alun-Alun. The Lahire Naga Tahun episode consists of 2 scenes, namely Alun-Alun and Alas.